2009
DOI: 10.1177/070674370905401004
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in Adults with Attention-Deficit Hyperactivity Disorder

Abstract: Objective: To examine the prevalence of comorbid Axis I (current and lifetime) and II disorders in adult men and women with attention-deficit hyperactivity disorder (ADHD). Method:Adult patients (n = 447; 266 men, 181 women) received comprehensive assessments for ADHD and Axis I and II disorders. Adults were aged between 17 and 74 years. Among the patients diagnosed with ADHD (n = 335), there were those with ADHD inattentive subtype (ADHD-I) (n = 199), hyperactive-impulsive subtype (ADHD-H) (n = 24), or combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
151
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(181 citation statements)
references
References 33 publications
21
151
3
6
Order By: Relevance
“…2 Previous studies have reported increased rates of comorbid substance abuse, anxiety, mood, personality, and disruptive behaviour disorders among adults with ADHD, persisting from childhood into adulthood. [3][4][5][6][7][8][9][10][11] Several studies have investigated the psychosocial characteristics of children in relation to accidental injuries. 12,13 Children with behavioural disorders were reported to exhibit a 1.5-times higher risk of injury compared with those without such disorders.…”
Section: Discussionmentioning
confidence: 99%
“…2 Previous studies have reported increased rates of comorbid substance abuse, anxiety, mood, personality, and disruptive behaviour disorders among adults with ADHD, persisting from childhood into adulthood. [3][4][5][6][7][8][9][10][11] Several studies have investigated the psychosocial characteristics of children in relation to accidental injuries. 12,13 Children with behavioural disorders were reported to exhibit a 1.5-times higher risk of injury compared with those without such disorders.…”
Section: Discussionmentioning
confidence: 99%
“…DEHB de panik bozukluğu ek tanısının erkeklerde daha sık izlendiği belirtilmektedir (Cumyn et al, 2009). …”
Section: Discussionunclassified
“…si olmayanlara göre daha yüksek oranda rastlanmış ve anksiyete bozukluklarının yüksek oranda eşlik ettiği, kadınlarda özellikle önceden geçirilmiş ya da halen var olan panik bozukluğu eştanısının daha yüksek oranlarda olduğu saptanmıştır (Cumyn et al, 2009). …”
unclassified
“…Se identificó, asimismo, que 31.7% de los pacientes presentaba un trastorno por déficit de atención e hiperactividad. Los estudios señalan una fuerte interrelación del trastorno por déficit de atención e hiperactividad con el de uso de sustancias, entre 15 y 50% (Cumyn, French, & Hechtman, 2009;Ochoa, Salvador, & Madoz-Gúrpide, 2010;Torrico Linares et al, 2012).…”
Section: Discusión Y Conclusionesunclassified